Bambara Groundnut: An Underutilized Leguminous Crop for Global Food Security and Nutrition - Tan, Xin Lin; Azam-Ali, Susan; Goh, Ee Von; Mustafa, Maysoun; Chai, Hui Hui; Ho, Wai Kuan; Mayes, Sean; Mabhaudhi, Tafadzwanashe; Azam-Ali, Sayed; Massawe, Festo (Frontiers in Nutrition, 2020)
Rapid population growth, climate change, intensive monoculture farming, and resource depletion are among the challenges that threaten the increasingly vulnerable global agri-food system. Heavy reliance on a few major crops is also linked to a monotonous diet and poor dietary habits and micronutrient deficiencies, which are often associated with diet-related diseases. Diversification – of both agricultural production systems and diet – is a practical and sustainable approach to address these challenges and to improve global food and nutritional security. This strategy is aligned with the recommendations from the EAT-Lancet report, which highlighted the urgent need for increased consumption of plant-based foods to sustain population and planetary health. Bambara groundnut (Vigna subterranea (L.) Verdc.), an underutilized African legume, has the potential to contribute to improved food and nutrition security, while providing solutions for environmental sustainability and equity in food availability and affordability. This paper discusses the potential role of Bambara groundnut in diversifying agri-food systems and contributing to enhanced dietary and planetary sustainability, with emphasis on areas that spans across the value chain: from genetics, agroecology, nutrition, processing and utilization, through to its socioeconomic potential. Bambara groundnut is a sustainable, low cost source of complex carbohydrates, plant-based protein, unsaturated fatty acids and essential minerals (magnesium, iron, zinc, and potassium), especially for those living in arid and semi-arid regions. As a legume, Bambara groundnut fixes atmospheric nitrogen to improve soil fertility. It is also resilient to adverse environmental conditions and can yield on poor soil. Despite its impressive nutritional and agroecological profile, the potential of Bambara groundnut in improving the global food system is undermined by several factors, including resource limitation, knowledge gap, social stigma, and lack of policy incentives. Multiple research efforts to address these hurdles have led to a more promising outlook for Bambara groundnut, however, there is an urgent need to continue researching into these areas of uncertainty. Based on current evidence, recommendations for future work are to: (i) continue crop and processing improvement, (ii) raise awareness and education, and (iii) expand market through innovation in product development and diversification.